RESEARCH ON MENTAL STATES OF ANXIETY OF FIRST-YEAR CADETS OF THE UNIVERSITY OF LIFE SAFETY - Popovych, Ihor; Tkach, Tamara; Sirko, Roksolana; Rudenko, Larysa; Sokolova, Hanna; Slobodianyk, Volodymyr; Blynova, Olena (Revista Inclusiones, 2020)
The purpose is to examine psychological structure, variables and correlation of the factors of mental states of anxiety of cadets. Adaptation of first-year cadets of the University of Life Safety plays a key role in the formation and development of a future specialist – a rescue worker. The methodology is based on the understanding of anxiety in two dimensions: psychological and physiological. The research results allow the administration of a higher education institution to understand psychological content parameters of mental state of anxiety of first-year cadets and operationalize the process of their adaptation. “Expressive-emotional anxiety” (44.04%), related to “content anxiety” (rs=-.177; p≤.01) and “distant anxiety” (rs=.164; p ≤ .01) are main factors in the structure of cadets’ mental states of anxiety. Mental states of anxiety affect the level and quality of a cadet’s knowledge. The obtained results can be useful for managers of educational process, directors and teaching staff of higher education institutions of life safety and also for researchers in psychology of anxiety.